Rendimiento diagnóstico del agar sangre con filtro versus agar karmali para el diagnóstico de Campylobacter en coprocultivo - Moya-Salazar, Jeel (2016)
Objective: To evaluate the diagnostic performance of blood agar with filter (BSA) in comparison with Karmali agar (AK) for the diagnosis of Campylobacter spp in stool culture. Material and methods: A cross-sectional prospective experimental research was carried out at the Hospital Nacional Docente Madre-Niño "San Bartolomé", where stool samples with functional stool examination reactive for inflammation were evaluated. The samples were seeded in ASF and AK and incubated up to 72 hours in microaerophilia. Species differentiation was performed with hippurate hydrolysis. Results: A total of 287 positive samples were collected. The isolation of Campylobacter in ASF and AK was 78.3% and 21.7%, respectively. Sensitivity was 90.9% for ASF. Mean growth time was 32.7 ± 11 hours (p<0.59) and contamination of culture media from positive patients was 61.7% for AK. 74.8% of non-jejuni Campylobacter species were isolated. Conclusions: Filter blood agar presents a higher diagnostic yield than Karmali Agar for Campylobacter isolation in a relatively shorter time and proving to be more cost-effective than selective isolation medium. In addition, Campylobacter non-jejuni was isolated mainly from neonates and infants, where most infections occur.